PELAYANAN PUBLIK PADAPUSAT KESEHATANMASYARAKAT DI KECAMATAN TAMPAN KOTA PEKANBARU TAHUN 2017 - Dita Sari; Baskoro Wicaksono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research is motivated by the many obstacles encountered in the Sidomulyo Public Hospital in Tampan District, Pekanbaru City, including: (1) not all doctors work every day, while nurses also enter alternately; and (2) the absence of pulmonary, child and neurologist specialists, even though previously there were.The theory used in this study is an indicator of public service according to Menpan Number 63 of 2003, namely: service procedures, service time, service costs, service products, facilities and infrastructure, and competence of service providers. This research is qualitative research, while the data collection techniques used are interview techniques.The results showed that public services at the community health center in Inpatient Hospital Sidomulyo Tampan District, Pekanbaru in 2017 were not optimal. Inhibiting factors for public services in community health centers (Puskesmas) in Tampan Subdistrict, Pekanbaru City In 2017 there was still a lack of human resources in Puskesmas, still lack of availability of Puskesmas facilities and infrastructure, not optimal maintenance, maintenance and inspection of infrastructure facilities, and not yet optimal supervision of Puskesmas facilities and facilities by the Pekanbaru City Health Service.Keywords: Public services, Puskesmas